2013
DOI: 10.1001/jama.2013.279201
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy With Gemcitabine and Long-term Outcomes Among Patients With Resected Pancreatic Cancer

Abstract: IMPORTANCEThe prognosis for patients with pancreatic cancer is poor, even after resection with curative intent. Gemcitabine-based chemotherapy is standard treatment for advanced pancreatic cancer, but its effect on survival in the adjuvant setting has not been demonstrated.OBJECTIVE To analyze whether previously reported improvement in disease-free survival with adjuvant gemcitabine therapy translates into improved overall survival. DESIGN, SETTING, AND PATIENTS CONKO-001 (Charité Onkologie 001), a multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
1,078
7
26

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,577 publications
(1,142 citation statements)
references
References 29 publications
31
1,078
7
26
Order By: Relevance
“…Adjuvant chemotherapy is considered the standard of care for patients with resectable pancreatic ductal adenocarcinoma. 6,7 Pyrimidine analogs (gemcitabine or 5-fluorouracil (5-FU)) are the most commonly used agents, with gemcitabine demonstrating an improved survival compared with no treatment in CONKO-001, 7 and an improved toxicity profile compared with 5-FU in ESPAC-3. 8 Molecular studies have shown that pancreatic ductal adenocarcinomas contain a high number of gene deletions, mutations, amplifications and rearrangements, 9,10 yet the contribution of these genetic abnormalities to tumor behavior and response to systemic therapy is not well understood.…”
mentioning
confidence: 99%
“…Adjuvant chemotherapy is considered the standard of care for patients with resectable pancreatic ductal adenocarcinoma. 6,7 Pyrimidine analogs (gemcitabine or 5-fluorouracil (5-FU)) are the most commonly used agents, with gemcitabine demonstrating an improved survival compared with no treatment in CONKO-001, 7 and an improved toxicity profile compared with 5-FU in ESPAC-3. 8 Molecular studies have shown that pancreatic ductal adenocarcinomas contain a high number of gene deletions, mutations, amplifications and rearrangements, 9,10 yet the contribution of these genetic abnormalities to tumor behavior and response to systemic therapy is not well understood.…”
mentioning
confidence: 99%
“…Die Prognose des Pankreaskarzinoms ist mit einer 5-Jahres-Überlebensrate von weniger als 5 % weiterhin unverändert schlecht. Nur 10-20 % der Patienten präsentieren sich mit lokal resektablen Tumoren bei Diagnosestellung und bei diesen Patienten führt eine Resektion gefolgt von adjuvanter Chemotherapie zu robusten 20 % 5-Jahres-Überlebensraten [23,25], in selektierten Patientengruppen auch 40 % bis hin zu über 50 % [2,11].…”
Section: Resektion Beim Fortgeschrittenen Pankreaskarzinom Nach Multiunclassified
“…Except for surgery, other treatments have shown modest impact on patients' survival and are often underutilized [3][4][5][6][7][8][9]. Since there are no cost-effective screening tests, a high clinical suspicion is necessary for the diagnosis of early stage tumors2 and the majority of patients are diagnosed with locally advanced or metastatic disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that survival of patients with PC has remained rather unchanged over the last decades with only 5-10% being alive after five years [4,10,11]. Besides established prognostic factors such as cellular differentiation, lymph vascular infiltration and tumor stage, there may be other reasons responsible for the low survival rate of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation